Analysis of the Relationship between Landuse and Non-point Source Pollution in Ashi River Basin - 马放 姜晓峰 王立 李哲 梁雄伟 (东华大学学报（英文版）, 2016)
Landuse is one of the most influential factors of non-point source pollution. Based on the three-year landuse data（ 2000,2005 and 2008）,Arc GIS and Fragstat were used to analyze the landuse type and the change of landscape pattern. The relationships between landuse and non-point source-total nitrogen（ NPS-TN） and nonpoint source-total phosphorus（ NPS-TP） were discussed with the methods of spatially statistical analysis,landscape pattern analysis and principal component analysis. The study results conveyed that agricultural land and forestland,which accounted for over 92% of the study area,were the major landuse type of Ashi River Basin.Meanwhile,the NPS pollution had close connections with landuse type and landscape pattern. When it comes to landuse type,the export risks of NPS-TN and NPS-TP were agricultural land 〉 urban land 〉 grassland 〉 forestland. As for landscape pattern,NPS-TN and NPS-TP were positively related to SHDI and SHEI, while negatively connected with LPI,AI and COHESION. Therefore,the study could reach the conclusion that the more fragmented and complicated the landscape patterns were,the more serious the NPS pollution was.